Management of Noble Moral Education for Madrasah Aliyah Students at Persatuan Islam Boarding School - Rohaeni, Anie; Wasliman, Iim; Rostini, Deti; Iriantara, Yosal (AGUSPATI Research Institute, 2021)
This research is due to concerns about the morals of students who graduate from Madrasah Aliyah who are in Persatuan Islam Boarding School environment which are still very vulnerable to being affected by environmental conditions that are not in accordance with the values upheld in the pesantren. The purpose of this study is to determine and analyze the Management of Noble Morals Education in Madrasah Aliyah Students at Persatuan Islam Boarding School. This research was conducted with a multi-case study approach at MA PPI 67 Benda Tasikmalaya, MA PPI 84 Ciganitri Bandung and MA PPI 99 Ran Brancho Garut with a qualitative method that management of noble character education in improving the quality of graduates of Madrasah Aliyah Islamic Boarding School students. The results of this study reveal that: (1) Noble character education management policies are based on harmonization of conventional Islamic boarding school values; (2) The noble character education program is based on the values of modern scientific development; (3) The implementation of noble character education, through activities that have been determined and serve as guidelines for the implementation of Islamic boarding school learning, as well as continuous monitoring or evaluation, both internally and externally in order to improve the quality of graduates; (4) The method used in the education of noble character that is applied by pesantren is precisely through example, conditioning (boarding school), direction (advice/nurturing), habituation (training and assignment), active participation (involvement of roles in activities) and learning with rewards. and punishments; (5) The form of noble character that is formed in noble character education, through cadres with precise character, scientific insight, competitiveness, tafaqquh fiddin and moral character; (6) The problems faced in noble character education related to combining the official curriculum and typical Islamic boarding schools must work together optimally; (7) The solution given in noble character education is the problem of time division between pesantren activities and learning in madrasas and boarding schools. The conclusion of this study is that the management of noble character education for MA PPI students is able to reduce the emotional turmoil of adolescent students and can become graduates with noble character, although it has not reached the expected degree.